Acute Osteoporotic Vertebral Fracture. Part 1. Definitions, Clinical Presentation, Pain Assessment, Diagnostic Imaging, Introduction to Differential Diagnosis - V. V. Lyalina; I. A. Borshenko; S. V. Borisovskaya; E. A. Skripnichenko; R. V. Binyakovskiy; V. V. Trishina; I. G. Nikitin (SINAPS LLC, 2022)
Osteoporosis is a widespread metabolic disease of the skeleton among the elderly. Osteoporotic fractures are significant manifestation of the disease, which can substantially affect the quality of life. The purpose of this article is to review approaches to the management of patients with acute osteoporotic fracture. This article consists of two parts. The first part reviews general information about osteoporosis, clinical course of osteoporotic fracture, differential diagnosis of pain syndrome, methods of visualization of fractures, differential diagnosis of osteoporosis. In the second part, we discuss differential diagnosis of osteoporotic fracture according to the data of imaging methods, non-pharmacologic, pharmacologic and surgical methods of treatment.